(untitled) - Jurkovic, Martin; Sosedova, Jarmila (Doprava a spoje, 2012)
Port development can refer either to the creation of a new port or to the expansion of an existing one, usually aimed to increasing its capacity or upgrading port operations. Main issue of port development is examined their current capacity and confronted it with the planned capacity.